PENGARUH KOMBINASI PIJAT PUNGGUNG DAN DZIKIR TERHADAP TEKANAN DARAH - Rudi Haryono; Iman Permana; Nur Chayati (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2017)
Background : Hypertensive patients increases every year. Studies on efforts to lower blood pressure in patients with hypertension continue to be developed, one of them with non-pharmacological therapy back massage and dhikr. The aim of this research was to reveal the influence of back massage and dhikr to blood pressure of hypertensive patient. Method : This research applied quasi experiment design by using pretest-posttest intervention with control group. The samples size were 60 respondents divided to 30 respondents as intervention group and 30 respondents as control group. The intervention group given was a back massage and dhikr as well as anti-hypertension therapy for 3 days consecutively while the control group was only given anti-hypertension therapy. Statistic Mann-Whitney test was used to analyze the influence of combination back massage and dhikr intergroup and Kruskal Wallis test was used to test the influence difference of combination of back massage and dhikr to blood pressure in the intervention group. Result : On the Mann-Whitney test showed back massage and dhikr was proven to decrease systole blood pressure (p=0,004) and did not influence the diastole blood pressure (p=0,987). Conclusion : Back massage and dhikr was proven to statistically significant decrease systole blood pressure. The combination, however, reduced diastole blood pressure statistically yet insignificant.